TINJAUAN HUKUM TINDAK PIDANA KORUPSI DAN PENYELEWENGAN KEKUASAAN OLEH PEJABAT NEGARA - Elizabeth Nanik Khrisnawati (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2021)
Efforts to combat corruption in Indonesia have been made in a variety of ways, but corruption continues to be perpetrated in a variety of ways by a variety of institutions, not least against village funds. The writing style is juridical-normative, with a statutory approach and examples of corruption in the village. Corruption poses a number of threats to society and individuals, the younger generation, politics, the nation's economy, and the bureaucracy. There are obstacles to combating corruption, including structural, cultural, instrumental, and management barriers. Corruption is defined as the unnatural behavior of public officials, including politicians and state employees, to enrich themselves or a nearby group by using the power entrusted to them, according to the law of eradicating corruption, which is one of the most important agendas in overcoming corruption cases of corruption criminal courts, which are institutions that are trusted to handle a case. Corruption investigates and decides on a case. Keywords: Village Fund, Corruption, History of Corruption, Law Enforcement of Corruption in Indonesia